Hypochloremia Is a Noninvasive Predictor of Mortality in Pulmonary Arterial Hypertension. Issue 5 (3rd March 2020) - Prins, Kurt W.; Kalra, Rajat; Rose, Lauren; Assad, Tufik R.; Archer, Stephen L.; Bajaj, Navkaranbir S.; Weir, E. Kenneth; Prisco, Sasha Z.; Pritzker, Marc; Lutsey, Pamela L.; Brittain, Evan L.; Thenappan, Thenappan
Abstract : Background: Pulmonary arterial hypertension (PAH) is a lethal disease. In resource‐limited countries PAH outcomes are worse because therapy costs are prohibitive. To improve global outcomes, noninvasive and widely available biomarkers that identify high‐risk patients should be defined. Serum chloride is widely available and predicts mortality in left heart failure, but its prognostic utility in PAH requires further investigation. Methods and Results: In this study 475 consecutive PAH patients evaluated at the University of Minnesota and Vanderbilt University PAH clinics were examined. Clinical characteristics were compared by tertiles of serum chloride. Both the Kaplan‐Meier method and Cox regression analysis were used to assess survival and predictors of mortality, respectively. Categorical net reclassification improvement and relative integrated discrimination improvement compared prediction models. PAH patients in the lowest serum chloride tertile (≤101 mmol/L: hypochloremia) had the lowest 6‐minute walk distance and highest right atrial pressure despite exhibiting no differences in pulmonary vascular disease severity. The 1‐, 3‐, and 5‐year survival was reduced in hypochloremic patients when compared with the middle‐ and highest‐tertile patients (86%/64%/44%, 95%/78%/59%, and, 91%/79%/66%). After adjustment for age, sex, diuretic use, serum sodium, bicarbonate, and creatinine, the hypochloremic patients had increased mortality when compared with the middle‐tertile and highest‐tertile patients. The Minnesota noninvasive model (functional class, 6‐minute walk distance, and hypochloremia) was as effective as the French noninvasive model (functional class, 6‐minute walk distance, and elevated brain natriuretic peptide or N‐terminal pro–brain natriuretic peptide) for predicting mortality. Conclusions: Hypochloremia (≤101 mmol/L) identifies high‐risk PAH patients independent of serum sodium, renal function, and diuretic use.